QUESTIONS USED IN PRIMARY EFL CLASSROOM DISCOURSE - Annastasia Permatasari; Josefa J. Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
This thesis is the study of types and functions of questions based on features of classroom discourse. In this study, the writer observed the types of questions that the English teacher used in General English classroom, and the functions of the questions based on features of classroom discourse. The data were collected through classroom observation and audio-recording of one class of the sixth grade. The theories applied are the teachers’ questions by Ellis (2008) and types of questions and features of classroom discourse by Walsh (2011). The qualitative approach was used in this study. The finding revealed that the teacher used two types of questions which were display questions and referential questions in the two meetings. Each meeting took 40 until 50 minutes. In addition, the teacher used three functions of questions based on features of classroom discourse, which are control of procedure, checking understanding, and eliciting a response. The finding also revealed that display questions have the function of checking understanding while referential questions have the functions of control of procedure, checking understanding and eliciting a response. In conclusion, questions can be considered as a tool for the teacher to check the students’ understanding and to elicit the students’ responses during teaching and learning process